Comparison of the Effectiveness of the Active Video Games and Sports Basic Games on the Development of Fundamental Motor Skills in Elementary School Students - Mansour Neisi; Sadegh Nasri; Rasool Abedanzadeh; Marzieh Balali (University of Tehran, 2021)
The aim of this study was to compare the effective of active video games and sports basic games on the development of fundamental motor skills in elementary school students. The method of the present study is semi-experimental with pretest-posttest design with control group. Sixty male students (age range: 8-11 years old) were selected by convenience sampling and randomly divided into two experimental groups (active video games (XbX), sports basic games) and a control group (inactive video games). The instruments used in this study are the Brunnicks-Ozertsky motor proficiency test, second edition, and the XbX 360 Kinect. First, participants performed motor skills pretest. Experimental groups performed the relevant training program for eight weeks, twice a week and 30 minutes per session. The control group also played passive video games under the full supervision of the Examiner with XbX console. At the end of the training sessions, the second edition of the Bruins Ozertsky motor proficiency test was repeated for all subjects (post-test phase). The results of the present study showed that active video and sports basic groups have a significant effect on the development of basic motor skills. Other results of this study showed that there is a significant difference between groups in the development of fundamental motor skills; these differences were significant with the traditional group, but significant differences were not found between the experimental groups. Therefore, it is recommended that coaches, in addition to sport basic trainings, they should also pay special attention to active video games.